CFD Study on Wire Mesh Inserts Enhancing Heat Transfer in Double Pipe Heat Exchanger - Parely, Rizky Nanda; Ruhyat, Nanang (Universitas Muhammadiyah Yogyakarta, 2025)
The efficiency of heat transfer in conventional double pipe heat exchangers (DPHE) was often limited by low heat transfer coefficients. This posed a challenge for compact-scale industrial applications requiring enhanced thermal performance without increasing system dimensions. One potential solution was the insertion of wire mesh inside the pipe to induce local turbulence and intensify forced convection. This study was conducted numerically using Computational Fluid Dynamics (CFD) in ANSYS Fluent 2024 R2. The DPHE consisted of concentric copper pipes with a length of 1240 mm, inner pipe diameter of 26/34 mm, and outer pipe diameter of 68/76 mm. Water was used as the working fluid in counterflow mode, with inlet hot water at 70 °C (Re 4000–16000) and cold water at 31 °C (Re 2000). The parameters varied were wire mesh angle (30°, 60°, 90°), wire spacing (3 mm, 4 mm, 5 mm), and mesh spacing (4 cm, 5 cm, 6 cm), arranged using an L9 orthogonal array. Three-way ANOVA and Tukey HSD test were applied to identify significant effects. The configuration of 30°, 3 mm, and 4 cm was found to be the most optimal, yielding a 34.55% increase in heat transfer compared to the plain DPHE.